What should we talk about? The authenticity of textbook topics. (24th March 2014) - Siegel, Aki
Abstract: Topics presented in textbooks and covered in language classrooms are crucial parts of language teaching, as they facilitate student engagement, willingness to communicate, and ultimately, learning. However, whilst researchers and practitioners frequently discuss the authenticity of the language in textbooks, the authenticity and usefulness of textbook topics are rarely discussed or evaluated. To investigate their authenticity, topics from ELT textbooks and naturally occurring conversations were collected, categorized, and compared. The conversations occurred in English between Japanese and non-Japanese students from ten different countries at a university dormitory in Japan. When the textbooks and conversations were compared, large discrepancies between the treatment of some topics became evident, including students' school lives. Pedagogic implications stemming from this review include incorporating topics that are realistic and practical for L2 English users into language classrooms to better prepare students for the 'world out there'.